Application Design For Office Stationary Inventory Management Based On Vb.Net At PT. Hunu Osias Padmada Eara Karawang - Yeny Rostiani; Indaryono Indaryono; Ratna Furi Handayani (LPPM STMIK Rosma, 2021)
The availability of office stationery is very important to make the required work smooth. In order for ATK management to be handled properly, an application is needed to manage ATK inventory data using a technology-based information system so that it becomes a complete information system. The method used by the author in conducting this research is the Waterfall model system development method starting from the specification of user requirements, planning, modeling, and coding. The method of specification of user requirements includes interviews, observations, literature studies, and documentation studies. The planning method includes the tasks to be carried out including the risks that may occur and the work schedule. Modeling methods include the design of flow documents, DFD, data dictionary, and ERD. The coding includes a program designer with the VB.Net programming language with SQL Server 2008 database and application testing using black box testing, namely this test is intended to determine whether the functions, inputs and outputs of the software are in accordance with the required specifications. To simplify reporting and recording so that errors do not occur, it is necessary to design and implement a system that can facilitate inter-related functions within the company by using Microsoft Visual Studio 2010 (VB.Net) and Microsoft SQL Server 2008. With the implementation of this system, it is expected will be useful for the company in its operations in the future.